2022
DOI: 10.1097/md.0000000000031151
|View full text |Cite
|
Sign up to set email alerts
|

The downward referral experiences of stroke caregivers in the regional medical alliance in China: A phenomenological study

Abstract: The downward referral platform in the regional medical alliance has provided more possibilities to follow-up rehabilitation and transitional care for increasing stroke survivors, which also has the most contributions in the rational use of resources and health promotion of stroke survivors. However the downward referral rate is low compared to upward referral. At present, no scholars have explored the downward referral experiences of medical demanders from the perspective of qualitative study, and these experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The transitional experience of PSD patients and their caregivers showed that the transfer of referral information between medical institutions at all levels needs to be improved. There was a lack of information sharing platforms between different levels of hoapitals and led to the fragmentation of patients’ health information [ 34 ], which may increase the frequency of swallowing function evaluation and the risk of aspiration. Discontinuous information transmission would also lead to a decline in patient satisfaction [ 35 ] and influencing the effectiveness of swallowing rehabilitation training.…”
Section: Discussionmentioning
confidence: 99%
“…The transitional experience of PSD patients and their caregivers showed that the transfer of referral information between medical institutions at all levels needs to be improved. There was a lack of information sharing platforms between different levels of hoapitals and led to the fragmentation of patients’ health information [ 34 ], which may increase the frequency of swallowing function evaluation and the risk of aspiration. Discontinuous information transmission would also lead to a decline in patient satisfaction [ 35 ] and influencing the effectiveness of swallowing rehabilitation training.…”
Section: Discussionmentioning
confidence: 99%
“…36,37 A better effect of medical alliances implementation maybe improve the basic medical service capabilities and management capabilities of CHCs, promote the rational allocation of medical staff, improve the satisfaction of medical staff, and enhance the basic and core capabilities of CHCs, which may have a positive impact on organizational performance. [38][39][40] In contrast, a poor effect of medical alliance implementation affects the improvement of the medical service capabilities of CHCs and cannot promote its development. Therefore this study proposes hypothesis 2: H2: The medical alliance implementation effect has a moderating effect on the process by which the organizational capabilities influence organizational performance of CHCs.…”
Section: Introductionmentioning
confidence: 99%